ACTIVITIES OF THE NATIONAL AVIATION UNIVERSITY UNDER THE CONDITIONS OF THE STATE OF MARTIAL - Zozulya, Serhii; Signayevskyi, Oleksandr; Gnatyuk, Viktor (Distance Education in Ukraine: Innovative, Normative-Legal, Pedagogical Aspects, 2023)
The article examines the activities of the National Aviation University under martial law. A brief description of the university is given, an analysis of the admissions campaign is carried out and a comparison of recruitment indicators of the current admissions campaign with previous periods. Also, modern information and communication platforms of the university, which are used to ensure the educational process, are described.